High brightness ultraviolet light-emitting diodes grown on patterned silicon substrate. (February 2019) - Robin, Yoann; Ding, Kai; Demir, Ilkay; McClintock, Ryan; Elagoz, Sezai; Razeghi, Manijeh
Abstract: We report on the fabrication of high brightness AlGaN-based ultraviolet light emitting diodes (UV-LED) on patterned silicon. Using the lateral epitaxial overgrowth approach, we demonstrate the growth of a 6 µm thick AlN layer of high crystalline quality. X-ray diffraction characterization showed a rocking curve with a full width at half maximum of 553 and 768″ for the (00.2) and (10.2) planes, respectively. The low dislocation density of the AlN template enabled the growth of bright AlGaN/GaN quantum wells emitting at 336 nm. By appropriate flip-chip bonding and silicon substrate removal processing steps, the patterned AlN surface was exposed and efficient bottom-emission UV-LEDs were realized. Improvement of the AlN quality and the structure design allowed the optical output power to reach the milliwatt range under pulsed current, exceeding the previously reported maximum efficiency. Further investigations of the optical power at different pulsed currents and duty cycles show that thermal management in this device structure is still challenging, especially in continuous wave mode operation. The strategy presented here is of interest, since AlN crystalline quality improvement and optimization of the light extraction are the main issues inhibiting efficient UV emitter on silicon fabrication.